Dosimetric comparison between dual-isocentric dynamic conformal arc therapy and mono-isocentric volumetric-modulated arc therapy for two large brain metastases - Uto, Megumi (J Radiat Res, 2018)
Mono-isocentric volumetric-modulated arc therapy (VMAT) can be used to treat multiple brain metastases. It remains unknown whether mono-isocentric VMAT can improve the dose distribution compared with dual-isocentric dynamic conformal arc therapy (DCAT), especially for two brain metastases. We compared the dose distribution between dual-isocentric DCAT and mono-isocentric VMAT for two large brain metastases, and analyzed the relationship between the distance between the two targets and the difference in dose distribution. A total of 19 patients, each with two large brain metastases, were enrolled. The dose prescribed for each planning target volume (PTV) was 28 Gy in five fractions (D(99.8) = 100%). We created new indices derived from conformity indices suggested by the Radiation Therapy Oncology Group (RTOG; mRTOG-CI) and Paddick et al. (mIP-CI), using the dosimetric parameters of the sum of the two PTVs. The median PTV was 5.05 cm(3) (range, 2.10–28.47). VMAT significantly improved mRTOG-CI and mIP-CI compared with DCAT. In all cases, VMAT was able to improve mRTOG-CI and mIP-CI compared with DCAT. Whereas the normal brain volume receiving 5 Gy was similar between the two modalities, the normal brain receiving 10, 12, 15, 20, 25 and 28 Gy (V(10)–V(28)) was significantly smaller in VMAT. The mean beam-on times were 213.3 s and 121.9 s in DCAT and VMAT, respectively (P < 0.001). Mono-isocentric VMAT improved the target conformity and reduced the beam-on time and V(10)–V(28) of the normal brain for not only two close metastases but also two distant metastases. Mono-isocentric VMAT seems to be a promising treatment technique for two large brain metastases.